Neutral and Climate-Driven Adaptive Processes Contribute to Explain Population Variation in Resin Duct Traits in a Mediterranean Pine Species - Vázquez-González, Carla; López-Goldar, Xosé; Zas, Rafael; Sampedro, Luis (Frontiers in Plant Science, 2019)
Resin ducts are important anatomical defensive traits related to biotic resistance in conifers. Previous studies have reported intraspecific genetic variation in resin duct characteristics. However, little is currently known about the micro-evolutionary patterns and adaptive value of these defensive structures. Here, we quantified inter-population genetic variation in resin duct features and their inducibility in Pinus pinaster and assessed whether such variation was associated with climate gradients. To that end, we characterized the resin duct system of 2-years-old saplings from 10 populations across the species’ distribution range. We measured axial resin duct features (density, mean size and percentage conductive area of resin ducts) and their inducibility in response to methyl jasmonate. Genotyping of single nucleotide polymorphisms allowed to account for the population genetic structure in our models in order to avoid spurious correlations between resin duct characteristics and climate. We found large inter-population variation in resin duct density and conductive area, but not in their inducibility. Our results suggest that population variation in the percentage conductive area of resin ducts likely arise from adaptation to local climate conditions. This study highlights the adaptive relevance of resin ducts and helps to shed light on the micro-evolutionary patterns of resin-based defences in conifers.